-2(y-1)(-y+5)=0

Thank you for the opportunity to help you with your question!

Step 1: Divide both sides by -2

-2 (y-1)(-y+5) / -2 = 0/-2

(y -1) (-y +5) = 0

Step 2: y - 1 = 0

Solve for y : Add 1 to both sides

y -1 +1 = 0+1

y = 1

or

-y + 5 = 0

Add -5 to both sides:

-y + 5 - 5 = 0 -5

-y = -5

Step 3: Multiply -1 to both sides:

-1 ( -y = -5)

y = 5

Ans: y = 1 or y = 5

Either answer would give the expression -2( y-1) (-y+5) = 0

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up